2012
DOI: 10.1074/jbc.m112.374710
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Interaction Site between Sortilin and the p75 Neurotrophin Receptor Reveals a Regulatory Role for the Sortilin Intracellular Domain in p75 Neurotrophin Receptor Shedding and Apoptosis

Abstract: Background: Sortilin and p75NTR induce neuronal apoptosis by binding pro-neurotrophins during development and following neuronal injury. Results: Sortilin interacts with an extracellular juxtamembrane 23-amino acid sequence of p75 NTR . Conclusion: Despite binding being mediated through extracellular interactions, the intracellular domain of sortilin regulates p75 NTR shedding and apoptosis. Significance: Mapping may allow design of compounds inhibiting neuronal cell death by blocking the interaction between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 34 publications
(24 reference statements)
1
35
0
Order By: Relevance
“…Previous work demonstrated that phosphorylation of the cation-independent mannose 6-phosphate receptor on the cytoplasmic tail, which has high sequence similarity to sortilin, directly associates with its exit from the TGN (45). Previous studies indicate that, while the extracellular domain of sortilin associates with direct receptor interactions, the intracellular domain regulates its biological effects (46). The present study, which shows that sortilin-dependent calcification requires posttranslational modification of the C-terminus, supports this notion.…”
Section: Discussionsupporting
confidence: 78%
“…Previous work demonstrated that phosphorylation of the cation-independent mannose 6-phosphate receptor on the cytoplasmic tail, which has high sequence similarity to sortilin, directly associates with its exit from the TGN (45). Previous studies indicate that, while the extracellular domain of sortilin associates with direct receptor interactions, the intracellular domain regulates its biological effects (46). The present study, which shows that sortilin-dependent calcification requires posttranslational modification of the C-terminus, supports this notion.…”
Section: Discussionsupporting
confidence: 78%
“…It seems reasonable to suggest that sorCS1b may also inhibit, or at least decrease, uptake of other soluble sortilin ligands that share the same binding site as α-Gal A and CNTF in the β-propeller domain of sortilin, e.g. As mentioned above sortilin associates with the p75 NTR , and engages both p75 NTR and pro-neurotrophins to form a death signalling trimeric complex [13,14,18,32]. Apart from soluble ligands, sortilin is also capable of interacting with other transmembrane proteins.…”
Section: Discussionmentioning
confidence: 98%
“…Cells were serum starved for 3 h and subsequently treated with 3 nM NGF for 10 min before lysis. Proteins were cross-linked on ice before lysis with the membrane-permeable protein cross-linker dithiobis(succinimidylpropionate) (Pierce) and were immunoprecipitated as described previously (55).…”
Section: Methodsmentioning
confidence: 99%